Novel Use of Silicone Sheets for Immediate Implant Placement in Fresh Molar Extraction Sockets - Won-Pyo Lee; Jae-Heung Choi; Sang-Joun Yu; Byung-Ock Kim (Hindawi Limited, 2019)
In the recent years, the immediate placement of dental implants into fresh extraction sites has become an acceptable treatment approach. However, immediate molar implant placement presents specific challenges because of the anatomical and physiologic limitations. Such implant surgeries commonly require procedures that use a barrier membrane to generate bone and soft tissue or one that seals the molar extraction socket through a coronally advanced flap. Here, as an alternative, we report a method for treating molar extraction socket wounds in the hard and soft tissues after immediate placement of an implant using a silicone sheet.